Neuroprotective effect of arctigenin against neuroinflammation and oxidative stress induced by rotenone. Issue 5 (10th January 2018) - Zhang, Na; Dou, Deqiang; Ran, Xiaoku; Kang, Tingguo
Abstract : The present study was to investigate the neuroprotective effect of arctigenin, the major active component of a traditional Chinese medicine "Arctii Fructus", against PD in a rat model induced by rotenone. Abstract : Background : the present study was to investigate the neuroprotective effect of arctigenin, the major active component of a traditional Chinese medicine "Arctii Fructus", against PD in a rat model induced by rotenone. Materials and methods : in the present study, rotenone was injected subcutaneously in the backs of rats to mimic the progressive neurodegenerative nature of PD and arctigenin was administered. Behavioral analyses including a grid test, bar test and open-field test were used to evaluate motor activities and behavioral movement abilities. Energy metabolism indexes including oxygen consumption, carbon dioxide production, heat production and energy expenditure were measured via a TSE phenoMaster/LabMaster animal monitoring system. Immunohistochemistry was performed to detect the staining of TH and the expression of α-synuclein in substantia nigra (SN). The effect of arctigenin on oxidative stress was evaluated by the levels of GSH and MDA, and activities of SOD and GSH-Px. The levels of pro-inflammatory cytokines such as IL-6, IL-1β, TNF-α, IFN-γ and PGE2, the expression of Iba-1 and GFAP, and the impression of inflammatory mediators such as COX-2 and NF-κB in the SN were measured to evaluate the effect on the inflammation of SN area induced by rotenone. Results : compared with the ROT group, the deadlock time of rats treated with arctigenin was significantly shortened and the score of locomotor activity increased in the behavioral test; the number of TH + positive DA neurons of the arctigenin treated group was increased and α-synuclein immunopositive was decreased; the level of GSH and activities of SOD and GSH-Px in the arctigenin-treated group were significantly increased; arctigenin administration induced a significant decrease in the MDA level; arctigenin also significantly decreased the levels of IL-6, IL-1β, TNF-α, IFN-γ and PGE2 and reduced the impression of COX-2 and NF-κB in SN; treatment with arctigenin decreased microglia and astrocyte activation evidenced by the reduced expression of Iba-1 and GFAP. Conclusion : the findings demonstrated that arctigenin can improve the behavior changes of PD rats and the damage of DA neurons. The oxidative stress and inflammation involved in the pathogenesis of PD and arctigenin may protect DA neurons through its potent antioxidant and anti-inflammatory activities.